Characterizations of bio-char from fast pyrolysis of Meranti wood sawdust - Mazlan, M.A.F. (Institute of Physics Publishing, 2015)
In this research, Meranti wood sawdust (MWS) was pyrolyzed in a fixed bed drop- type pyrolyzer under an inert condition. The first part of the study is to determine the influence of pyrolysis temperature (450, 500 and 550 °C) on the yield of pyrolysis products. Pyrolysis of the waste MWS material generated the highest amount of bio-char with approximately 38 wt. at pyrolysis temperature of 450 °C. Next, the char product (from pyrolysis at 450 °C) was analyzed to compare its characteristics with the raw MWS feedstock. The major component of the char is carbon element, significantly contributed to its high calorific value. TGA profile shows the MWS char could withstand high temperature of up to 400 °C. Under extensive heating, particle size of the bio-char from SEM images decreased due to breakage and shrinkage processes. © Published under licence by IOP Publishing Ltd.